Distinguishing Healthy from Otosclerotic Ears: Effect of Probe-Tone Frequency on Static Immittance - Shahnaz, Navid; Polka, Linda (Journal of the American Academy of Audiology, 2002)
The diagnostic utility of static immittance (SI) with respect to distinguishing healthy from otosclerotic ears was investigated at different probe-tone frequencies in 68 healthy ears and 36 ears with surgically confirmed otosclerosis. Because one effect of otosclerosis is to shift the resonant frequency of the middle ear to higher values as a result of increased stiffness of the middle ear system, it was hypothesized that SI measured at higher probe-tone frequencies may provide a better distinction between healthy and otosclerotic ears. As expected, the results of this study indicate that SI measured at higher probe-tone frequencies is superior to a standard low probe tone in the detection of otosclerotic ears. Through systematic and objective comparisons of relevant probe-tone frequencies using both group statistics and test performance analysis, the present study suggests 630 Hz as an optimum probe-tone frequency for measuring SI with respect to distinguishing healthy ears from otosclerotic ears.
Keywords: Immittance; middle ear; otosclerosis; resonance; tympanometry